DIAGNOSIS AND TREATMENT OF MUCORMYCOSIS: AN INTRUDER POST-COVID-19 - Kesharwani, Disha; Mishra, Sandhya; Verma, Bhumika; Verma, Kamini; Suraj Banjare (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Mucormycosis can be elaborated as mycosis due to Mucorales. Mucormycosis is an angioinvasive infection. Fungi of Mucorales order is the causative organism of mucormycosis and pertains to the class of zygomycetes. It is ordered on number third after candidiasis and aspergillosis in the category of invasive mycosis. Rhizopus arrhizus (oryzae) is the most important species which cause this disease. It is categorized as a disease with high mortality. There is a 46% chance of mucormycosis with person having sinus infection, 76% of chances with pulmonary infection, and 96% for disseminated Mucormycosis. The COVID-19 pandemic precipitated this disease in a common way. Around 90% of the population was exposed to coronavirus disease 2019 (COVID-19) infection during the pandemic which ultimately affected the immunity of individual, leading to increased chance of exposure to other infectious disease. Mucormycosis is one of such disease which can highly affect the individual with COVID-19 infection in patient’s history. This review presents a brief about the disease origin, occurrences, types, signs and symptoms, risk factors, diagnosis, and treatments available, along with recent patents. This review also elaborated the treatment of COVID-19-associated mucormycosis and other risk factors. It was found that the diagnosis is not simple and easy sometimes it was observed postmortem also. This review also focuses on various methods with which easy diagnosis of this dreadful disease can be done.